Diagnosis and treatment of chronic gingivostomatitis in 12 cats - Sánchez-V, Mauricio; Vélez-Velásquez, Paula; Correa-Valencia, Nathalia M (Revista Colombiana de Ciencias Pecuarias, 2025)
Anamnesis: A descriptive series of 12 cats diagnosed with feline chronic gingivostomatitis (FCGS) was conducted to describe the lesions and clinical features. Two of them were treated with surgical tooth extraction. Clinical findings: All patients exhibited generalized gingivitis and marked halitosis, and four of them showed proliferative tissue. Seven cats tested positive for Bartonella spp. through molecular testing (qPCR), two were positive for Mycoplasma spp., two for Hepatozoon spp., and one for filariae. Three patients tested positive for at least two hemopathogens. All the patients tested negative for Babesia spp. and Rickettsiales. Therapeutic approach: Among all the patients, two (patients 4 and 7) underwent the surgical treatment of choice for the disease, which involved extraction of incisors, premolars, and molars, according to the recommendations of the specialist veterinarian and with the consent of the owners. Results and conclusion: Successful results were obtained for both cats surgically treated, with proper healing and increased food intake during the first two weeks after treatment.